A REVISION OF MALAYSIAN BAUHINIEAE - de Wit, H. C. D. (Research Center for Biology, 1956)
This revision deals with the tribus Bauhinieae(Caesalpiniaceae)as occurring in Malaysia.The tribe includes the genera Bauhinia L. s.str., Bracteolanthus de Wit gen. nov., Gigasiphon Drake del Cast.,Lasiobema (Korth.) Miq., Lysiphyllum (Benth.)de Wit gen. & stat. nov., Phanera Lour.,and Piliostigma Hochst. Bauhinia is reduced to the original Lin-nean delimitation; 9 species are treated (inclusive of a number of varieties) ; 2 species are reduced to the rank of varieties and 3 new varieties are described, accounting for 3 new varietal combinations and 3 new varietal names.Bracteolanthus contains a single species for which a new combination is proposed. Gigasiphon is represented by 3 species; 3 new specific combinations are made.Lasiobema is represented by 5 species; in this ge- nus 1 new species is described, 4 new combinations and 1 new varietal combination are proposed,and a new but insufficiently represented species is recorded.Some new combinations for extra-Malaysian species are also proposed.Of Lysiphyllum 2 species are treated; 2 new combinations and some new combinations for extra-Malaysian species were necessary.Pha-nera is by far the largest genus:44 species,many of which are divided into subspecies and/or varieties.The genus is subdivided into three sub-genera, Phanera,Biporina de Wit, and Austrocercis de Wit.Of these,subgenus Phanera, in its turn, contains 3 sections, all new, viz Pha.nero-siphon, Meganthera, and Micranthera.Subgenus Biporina comprises the 3 new sections Bifoliola, Palmatifolia,and Cinnamomifolia. Subgenus Austrocercis consists of a single species.The recognition of Phanera as a genus, as well as the description of new taxa and the revaluation of some previously described ones made necessary a large number of new names and new combinations.